أثر برنامج تدريبي مقترح بطريقة التدريب الدائري في تنمية صفة القوة الانفجارية والسرعة الانتقالية لدى لاعبي كرة القدم صنف أواسط. - حمودي, علاء الدين; شنوف, خالد; لوح, هشام (جامعة الوادي - University of Eloued, 2021)
تهدف الدراسة التي بين أيديكم إلى معرفة تأثير البرنامج التدريبي المقترح بطريقة التدريب الدائري لتنمية صفة القوة الانفجارية والسرعة الانتقالية لدى لاعبي كرة القدم، ولأجل ذلك اتبعنا المنهج التجريبي لملائمته مع طبيعة الدراسة، حيث بلغت عينة الدراسة 14 لاعبا صنف أواسط من فريق إتحاد ألرمشي بولاية تلمسان، والتي اختيرت بطريقة قصديه، واستعملنا لجمع البيانات اختبارات قبلية وبعدية للقوة الانفجارية والسرعة الانتقالية، وجاءت أهم نتائج الدراسة أن للبرنامج التدريبي المقترح أثر إيجابي على صفتي القوة الانفجارية والسرعة الانتقالية، إضافة إلى أن التدريب بصفة القوة الانفجارية يؤثر على تنمية صفة السرعة الانتقالية عند لاعبي كرة القدم صنف أواسط. -Abstract : The Study Aims At Knowing The Effect Of The Proposed Training Program With The Use Of Training Circle To Develop The Quality Of Explosive Power And Transitional Speed For Foot Ball Player, For This Reason We Follow The Experimental Approach For Its Suitability With The Nature Of Study, The Sample Population Reached 14 Middle Class Player From Remchi Team In Tlemcen City Which Is Chosen Intentionally And We Used To Collect Data Pre And Post Tests For Explosive Power Transitional Speed, The Most Important Results Of The Study Indicated That The Proposed Training Program Had A Positive Impact On Explosive Power And Transitional Speed Moreover, The training By The Quality Of Explosive Speed Effects On Development The Quality Of Transitional Speed For middle Class Foot Ball Player.
Title of the article, The Effect Of The Proposed Training Program By Circle Training Method To Develop Quality Of Explosive Power And Transitional Speed For Middle Class Foot Ball Players.
مقال
Keywords: Program, Training, Circle Training, Explosive Power, Transitional Speed, Foot Ball Player, Adolescence; .البرنامج، التدريب، التدريب الدائري، القوة الانفجارية، السرعة الانتقالية، لاعب كرة القدم، المراهقة